Oli2go: an automated multiplex oligonucleotide design tool. Issue Volume 46:Issue W1(2018) (30th April 2018) - Hendling, Michaela; Pabinger, Stephan; Peters, Konrad; Wolff, Noa; Conzemius, Rick; Barišić, Ivan
Abstract: The success of widely used oligonucleotide-based experiments, ranging from PCR to microarray, strongly depends on an accurate design. The design process involves a number of steps, which use specific parameters to produce high quality oligonucleotides. Oli2go is an efficient, user friendly, fully automated multiplex oligonucleotide design tool, which performs primer and different hybridization probe designs as well as specificity and cross dimer checks in a single run. The main improvement to existing oligonucleotide design web-tools is that oli2go combines multiple steps in an all-in-one solution, where other web applications only accomplish parts of the whole design workflow. Especially, the oli2go specificity check is not only performed against a single species (e.g. mouse), but against bacteria, viruses, fungi, invertebrates, plants, protozoa, archaea and sequences from whole genome shotgun sequence projects and environmental samples, at once. This allows the design of highly specific oligonucleotides in multiplex applications, which is further assured by performing dimer checks not only on the primers themselves, but in an all-against-all fashion. The software is freely accessible to all users at http://oli2go.ait.ac.at/ .